2012
DOI: 10.1186/1746-6148-8-248
|View full text |Cite|
|
Sign up to set email alerts
|

Urine neutrophil gelatinase-associated lipocalin (NGAL) as a biomarker for acute canine kidney injury

Abstract: BackgroundBiomarkers for the early prediction of canine acute kidney injury (AKI) are clinically important. Recently, neutrophil gelatinase-associated lipocalin (NGAL) was found to be a sensitive biomarker for the prediction of human AKI at a very early stage and the development of AKI after surgery. However, NGAL has not yet been studied with respect to dog kidney diseases. The application of NGAL canine AKI was investigated in this study.ResultsThe canine NGAL gene was successfully cloned and expressed. Poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
81
3
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 27 publications
3
81
3
4
Order By: Relevance
“…4,24,25,26 Similar efforts are underway in veterinary medicine and show great promise. [28][29][30][31][32][33][34][35][36] (See also, Yerramilli in this issue) An AKI biomarker should be detectable in urine and/or plasma such that it can be assessed routinely and serve as an indicator of kidney function or dysfunction or response to injury. The ideal marker should reflect kidney specific events, be unique and specific to the kidney, and reflect very early and potentially sustained phases of the pathogenesis and repair processes.…”
Section: Identification Of Progressive Ckd: the Search For Active Injmentioning
confidence: 99%
See 1 more Smart Citation
“…4,24,25,26 Similar efforts are underway in veterinary medicine and show great promise. [28][29][30][31][32][33][34][35][36] (See also, Yerramilli in this issue) An AKI biomarker should be detectable in urine and/or plasma such that it can be assessed routinely and serve as an indicator of kidney function or dysfunction or response to injury. The ideal marker should reflect kidney specific events, be unique and specific to the kidney, and reflect very early and potentially sustained phases of the pathogenesis and repair processes.…”
Section: Identification Of Progressive Ckd: the Search For Active Injmentioning
confidence: 99%
“…29,30,31,34 (Figure 3) In dogs with naturally acquired urinary tract disease, urinary NGAL was a highly sensitive and specific predictor of AKI including dogs categorized as IRIS AKI Grade I. 30 In collaboration with IDEXX Laboratories, the one of the authors c similarly has …”
Section: Kidney Injurymentioning
confidence: 99%
“…In dogs, based on NGAL concentration, AKI can be predicted as early as 12 hours after surgery,26 and NGAL has been shown to increase in X‐linked hereditary nephropathy 27. In dogs with naturally occurring kidney disease, the uNGAL‐to‐creatinine ratio has been used to diagnose AKI 28.…”
mentioning
confidence: 99%
“…Despite the recommendation to administer intravenous fluids, N-acetyl cysteine, ascorbic acid, and some vasodilatory agents, no method exists to reliably prevent CIN [5][6][7], although some research has been done with the aim of detecting acute renal failure (ARF) and CIN in a timely manner [8][9][10].…”
mentioning
confidence: 99%
“…Studies have demonstrated that NGAL is a marker having a high sensitivity and specificity for the prediction of acute renal injury [12,13]. Lee et al demonstrated in an animal model that urinary NGAL level increased significantly earlier than serum creatinine level in the event of acute renal injury [8]. Padhy et al reported that NGAL peaked at 4 th hour and returned to normal by 48 th hour in CIN after coronary angiography [14].…”
mentioning
confidence: 99%